Raman Microspectroscopy of Individual Algal Cells: Sensing Unsaturation of Storage Lipids in vivo - Kotas, Petr (Jihočeská univerzita, 2013)
We have demonstrated the potential of Raman microspectroscopy for the fast and spatially resolved characterization of the composition of selected intracellular regions in individual living cells of three algal species. In particular, we have focused on lipid storage bodies and quantified the degree of unsaturation of algal lipids (iodine value). To verify our results, we developed a method for extraction of storage lipids from highly resistant Trachidiscus minutus cells and determined the fatty acid composition using GC/MS. We have found Raman microspectroscopy to be a fast, versatile, and virtually non-invasive tool for evaluating the potential of different algal species for algal lipid engineering and industry.
Raman Microspectroscopy of Individual Algal Cells: Sensing Unsaturation of Storage Lipids in vivo
Keywords: Raman spectroscopy; algal cells; lipids; iodine value; Raman spectroscopy; algal cells; lipids; iodine value